Sugar, cigars, and revolution : the making of Cuban New York - Pérez, Lisandro (New York University Press Books, 2018)
More than one hundred years before the Cuban Revolution of 1959 sparked an exodus that created today's prominent Cuban American presence, Cubans were settling in New York City in what became largest community of Latin Americans in the nineteenth-century Northeast. This book brings this community to vivid life, tracing its formation and how it was shaped by both the sugar trade and the long struggle for independence from Spain. New York City's refineries bought vast quantities of raw sugar from Cuba, ultimately creating an important center of commerce for Cuban émigrés as the island tumbled into the tumultuous decades that would close out the century and define Cuban nationhood and identity.